CEREBRAL ABSCESS WITH HYDROCEPHALUS MANIFESTATION: A CASE REPORT IN 10-MONTH-OLD INFANT - NUNKI PUSPITA UTOMO; MERARI PANTI ASTUTI (Faculty of Medicine Universitas Kristen Duta Wacana, 2023)
Background Alongside hydrocephalus, cerebral abscess poses as space-occupying lesion altering consciousness and intracranial pressure. Cerebral abscesses commonly presented vague clinical symptoms in infants, including weeks of fever and late-onset neurologic deterioration. However, limited studies denote cerebral abscesses, especially in children under one year old.Â Objective We reported a case of a 10-month-old male infant with cerebral abscess and hydrocephalus.Case description A 10-month-old male infant was taken to the hospital due to 6 days progressing fever. Neither clinical nor laboratory findings were abnormal. After being discharged from the hospital, the patient has admitted again 2 days later, reserved for 5 days of fever until unfortunate symptoms of raised intracranial pressure coincide with hypothermic body temperature. A brain CT-Scan showed an area of hypodense lesion in the parieto-occipital region suspected of brain abscess- resulting in non-communicating hydrocephalus. After a total of 12 days of intensive treatment with antibiotics, anti-convulsant, and steroid agents, the patient was comatose and passed away due to respiratory failure.Â Conclusion Brain abscesses should be investigated thoroughly despite the probable absence of a pathognomonic feature. Radiology imaging ought to demonstrate the early process of abscess pathogenesis. To the best of our knowledge, this is the first case report published in Indonesia of an infant with a cerebral abscess resulting in hydrocephalus.